Modern challenges of education and psychology of personality formation - Shpak A. S., Shpak T. V., Kuznetsova V. E., Ivanova M. E., Starkova E. N., Avilova V. V., Kulikova N. V., Mikhalchenkova N. A., Pankrateva S. G., Rezak E. V., Zalunin V. I., Pantseva E. I., Kisliakova O. P., Snezhkina L. P., Khazova A. A., Sokolova G. A., Lysenko V. V., Kostenko E. G., Ambartsumian N. A., Sudakov D. V., Sudakov D. V., Sudakov O. V., Nazliev D. K., Belov E. V., Iakusheva N. V., Belov E. V., Sudakov O. V., Shevtsov A. N., Shevtsov A. N., Iordanov K. B., Markov N., Akbarova S. N., Skibo T. I., Matveichik T. V., Chernyshev V. P., Timoshkov E. V. (Modern challenges of education and psychology of personality formation, 2020)
in the present work reveals the place and importance environmental problems in system of global problems of modern civilization, describes the main stages of the evolution of environmental knowledge, determined the driving forces and sources of the emergence and development of social ecology; presents the author's point of view on the object, subject, structure, functions and methods of social ecology as an integrative science and academic discipline.
Keywords: экология; ecology; экологическая проблема; глобальные проблемы современности; экологическая катастрофа; социально-экологический кризис; социальная экология; движущие силы социальной экологии; источники социальной экологии; объект социальной экологии; предмет социальной экологии; структура социальной экологии; функции социальной экологии; методы социальной экологии; global problems of our time; ecological problem; ecological catastrophe; socio-ecological crisis; social ecology; driving forces of social ecology; sources of social ecology; object of social ecology; subject of social ecology; structure of social ecology; functions of social ecology; methods of social ecology